Revista EmQuestão Vol. 17, n. 2 (2011) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2013)
Revista EmQuestão Vol. 17, n. 2 (2011)Link de acesso ao númerohttp://seer.ufrgs.br/EmQuestao/issue/view/1500/showToc